Perception of Graduates of Education Study Programs towards the Teaching Profession and Teacher Professional Education - Hana Mumtazia Nurhaq; Yaya Sunarya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The choice of study program is crucial in determining future career choices. Perceptions about a profession can influence a person's interest in choosing that profession. This study aims to describe the perceptions of graduates of the Education study program towards the teaching profession and Teacher Professional Education (PPG). This research used a descriptive qualitative method. The data sources in this study were 75 respondents who were graduates of the Education Field Study Program in the last five years (2019 to 2023). The data studied in this study were obtained using a semi-open questionnaire method and interviews. The results of this study are 1) there is a decrease in the perception of graduates of the Education field study program before and after experience in the world of education; 2) there are three main factors in choosing teaching as a profession, namely internal, external, and altruistic; 3) PPG is positively perceived, especially for improving self-professionalism and obtaining teacher certification to get incentives and a more decent career path.